Contribuição para ampliação da formação de arquitetos e urbanistas no manejo sustentável de águas pluviais - Parra, Geovana Geloni (2022)
It is important that cities keep up with technological developments that enable more sustainable urban planning. Despite the professional attributions defined by Brazilian Federal Law No. 12,378 of December 31, 2010, which regulates the practice of Architecture and Urbanism, the number of qualified and experienced professionals to deal with project and planning actions integrated to the sustainable management of rainwater is still is restricted in Brazil. Considering that many architects and urban planners enter the job market without having sufficient knowledge for this type of planning, it is essential that Architecture and Urbanism courses include in their curriculum the study of sustainable management of rainwater, instead of only conventional drainage processes. The present work aims to analyze and discuss how the sustainable management of urban rainwater has been addressed in the training of Architects and Urbanists at the national level and to propose guidelines for its incorporation in the training of qualified professionals. The work method consists of reviewing the literature on the subject, verifying the experiences of national and international Architecture and Urbanism courses, and identifying professionals who are working as professors in Universities. As a result, 2 courses were found that address LID and WSUD concepts within their curriculum and 13 courses that address Green Infrastructure, in addition, a difference was found within the training structure of international courses with Brazilian courses, these presenting a much more generalist training. After understanding all the results of the analysis of the pedagogical plans of the courses, it was possible to elaborate a suggestion of guidelines and teaching plans that contemplate the most sustainable management of rainwater integrated with Architecture and Urbanism. These suggestions were divided into 5 major areas: Architectural Design; Urbanism Project; Urban planning; Landscaping and Technological Areas Project. Finally, it is important to conclude that it is necessary to incorporate content into curriculum, mainly related to hydrology, that teachers are trained to be able to teach this concept of integrated planning to rainwater management and that the bibliographic references used are updated so that they add concepts more sustainable.